GDF15/MIC1 and MMP9 Cerebrospinal Fluid Levels in Parkinson's Disease and Lewy Body Dementia. - Walter Maetzler; Willy Deleersnijder; Valérie Hanssens; Alice Bernard; Kathrin Brockmann; Justus Marquetand; Isabel Wurster; Tim W Rattay; Lorenzo Roncoroni; Eva Schaeffer; Stefanie Lerche; Anja Apel; et al. (PLoS ONE, 2016)
Based on animal and ex-vivo experiments, Growth/Differentiation Factor-15 (GDF15, also called Macrophage Inhibitory Cytokine-1, MIC1), a member of the transforming growth factor-beta family, and Matrix Metalloproteinase-9 (MMP9), a member of the matrix metalloprotease family may be potential markers for Lewy body disorders, i.e. Parkinson's disease with (PDD) and without dementia (PDND) and Lewy body dementia (DLB). GDF15 has a prominent role in development, cell proliferation, differentiation, and repair, whereas MMP9 degrades, as a proteolytic enzyme, components of the extracellular matrix. In this study, cerebrospinal fluid GDF15 and MMP9 levels of 59 PDND, 17 PDD and 23 DLB patients, as well as of 95 controls were determined, and associated with demographic, clinical and biochemical parameters. Our analysis confirmed the already described association of GDF15 levels with age and gender. Corrected GDF15 levels were significantly higher in PDD than in PDND patients, and intermediate in DLB patients. Within Lewy body disorders, GDF15 levels correlated positively with age at onset of Parkinsonism and dementia, Hoehn & Yahr stage and cerebrospinal fluid t-Tau and p-Tau levels, and negatively with the Mini Mental State Examination. Remarkably, it does not relevantly correlate with disease duration. MMP9 was not relevantly associated with any of these parameters. Cerebrospinal GDF15, but not MMP9, may be a potential marker of and in Lewy body disorders.